2017
DOI: 10.1016/j.asmart.2016.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Anterior cruciate ligament remnant and its values for preservation

Abstract: Controversy surrounds the remnant-preserving anterior cruciate ligament surgery. Advantages of remnant preservation have been reported in regard to better healing and knee function, although no consensus has been reached. This review article discussed the value and meaning of anterior cruciate ligament remnant preservation in several sections such as effects on healing, remnant classification, biomechanical evaluation, relation to proprioception, animal studies, and clinical studies. We hope that this review w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 46 publications
0
22
0
1
Order By: Relevance
“…[1,[15][16][17][18]. Furthermore, the strength of the remnant tissue in the early phase after reconstruction may be beneficial for rehabilitation and early incorporation [19]. Nagai et al [20] reported that ACL remnants partially contributed to anterior-posterior stability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1,[15][16][17][18]. Furthermore, the strength of the remnant tissue in the early phase after reconstruction may be beneficial for rehabilitation and early incorporation [19]. Nagai et al [20] reported that ACL remnants partially contributed to anterior-posterior stability.…”
Section: Introductionmentioning
confidence: 99%
“…Nagai et al [20] reported that ACL remnants partially contributed to anterior-posterior stability. For these reasons, it would be better to provide a retensioning method to create a mechanically stable environment as possible [19].…”
Section: Introductionmentioning
confidence: 99%
“…5,10, [18][19][20][21][22] The purpose of preservation is to maintain its original anatomical and biomechanical properties. 19,21 Kirizuki et al 5 have showed that the nonreattached remnant type (Crain 4) in the subacute phase after injury has a higher healing potential. Haviv et al 4 have reported that during the first 3 months from injury the gross morphological features of the torn ACL remnant showed no scar (Crain 4) followed by scarring of the femoral remnant at first to the femoral notch, and eventually to the PCL (Crain 1) within 6 months from injury.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, negating the requirement for autografts would theoretically solve troublesome donor site morbidity issues such as loss of hamstrings strength and anterior knee pain. Current practices and trends towards remnant preservation and some of the improvements shown in subjective proprioceptive outcomes, knee stability and revision rate (Takazawa et al 2013 ; Takahashi et al 2016 ; Muneta and Koga 2017 ; Andonovski et al 2017 ) can be extrapolated to offer hypothetical benefits for primary repair over reconstruction.…”
Section: Anterior Cruciate Ligament Injuriesmentioning
confidence: 99%